Banking Tendencies in Offshore Banking - Bikas, Egidijus (Ekonomika, 2002)
Lots of small countries planned that having established financial offshore banking centres it would be easier to attract foreign banks, increase employment of local inhabitants, the country would be able to rise its standard of living and economical development of the country. That’s why these countries offered favourable financial conditions, lower taxes and weaker regulation and supervision of business. Banking in offshore banking is perfectly regulated business field. According to the age it is a very young field of banking business. It was found not just because of a well coordinated plan, but as well as of a development in peculiar conditions and certain stages. Banks in offshore banking gained a wide acknowledgement in a worldwide banking society. This business in offshore banking is the most dynamic part of international finance system. Gradually new money streams from the whole world abandon countries that have high taxes and intrude into banks registered in exotic countries. Reasons arc very simple: banks in offshore banking give wide compatitabile spectral of service, opportunity to increase profit, decrease taxes, get a loan in low interests, ensure high confidential level when fulfilling banking operations. Financial offshore banking centres attract those who hopes to avoid taxes hiding the biggest part of their property in favourable jurisdictions, which grant confidential and laws do not foresee responsibility for not paying taxes in the other country. So, offshore banking financial system is especially important and characteristic element of modem worldwide financial system. It conditions of growing tendencies of banking in offshore banking in global economic. Banking business is not just defined by laws in offshore banking, but also it is not separable part of global financial system and has an independence status. International currency fond defines financial offshore banking centres as financial systems where foreign assets and responsibilities of operating banks exceed volume of operations of current account. During the last decade almost all world large banks opened their sections in financial offshore banking centres. Banking in offshore banking is an international banking business in favourable regime. It plans potential differences of national laws, low establishment and controlling expenses, as well as electronic means of communication. Since nowadays money and other documents of payment are easily coded, ensured speed and accuracy of service and confidential of banking operations and effective control of these banks is not being executed, it forms favourable opportunities for money laundering concealing the origin of means and the right of property. Regulation system of business of offshore banking ensures widely reachable financial services for ordinary commercial banks, transnational corporations, legal and natural persons, so much for establishers of these banks and their customers.